Project Management Practices and Implementation of Projects in Manufacturing Companies in Rwanda. A Case of Inyange Industry Ltd. - Jessica , Uwera (International Journal of Scientific Research and Management (IJSRM), 2023)
Achievement of a project means that a number of its perceived factors were attained. It is not guaranteed that project management practices will result to proper implementation of projects by manufacturing companies. However, the success of projects largely depends on the way it is managed and controlled. The challenges met during the implementation of project management practices has been during project planning, exceeding the set budget and going beyond its set schedule and poor quality. The general objective of the study is to investigate the influence of project management practices on the implementation of projects in manufacturing companies in Rwanda, Kigali city. The study’s specific objectives are to examine how stakeholder participation, leadership support, communication and resource allocation influenced project implementation. The study will anchored by stakeholder theory, resource based view theory and cybernetics theory. The adopted a descriptive research designs. The target population was 73 manufacturing companies from the Inyange industry ltd. The targeted respondents were 73 comprising of employees from different departments. The study used stratified sampling method to ensure that all cases are well represented and use simple random sampling method to select the respondents. Leadership support is considered one of the critical success factors in project implementation; effective executive involvement can significantly improve project success. Maintaining open, regular and accurate channels of communication with all levels of project staff and stakeholders is vital to ensuring the effective implementation of capital expenditure projects. Allocation of resources helps managers to bring together more productive and effective project teams and workgroups and enables them to appraise their schedules and easily estimate resource availability in real-time. Key word: Stakeholder Participation, Leadership Support, Communication, Resource Allocation